Ferroelectric ceramic material with large dielectric constant in wide temperature range and preparation method thereof
By designing the stacked composite structure of the BZT-xBST ceramic embryo body, using the characteristics of critical ferroelectric phase transition, ferroelectric ceramic materials with large dielectric constants in a wide temperature range of 5℃ to 55℃ are prepared, which solves the problem of difficult to achieve both dielectric constant and temperature stability in the prior art, and achieves the stability of high dielectric performance and the wide temperature range.
Patent Information
- Application Number
- CN202411820566.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
When existing high-dielectric constant capacitors change in temperature or increase in voltage, the dielectric constant and capacitance value are easily changed, resulting in unstable performance and difficult to take into account both high dielectric constant and temperature stability.
By designing the overlapping composite structure of the BZT-xBST ceramic embryo body, using the characteristics of critical ferroelectric phase transformation, the group distribution ratio is accurately adjusted, and ferroelectric ceramic materials with large dielectric constants in a wide temperature range of 5°C to 55°C were prepared.
It is achieved to maintain high dielectric performance in a wide temperature range, and the dielectric constant is stable above 21448 in the range of 5°C to 55°C, filling the gap in existing materials that are difficult to obtain both in the wide temperature range and high dielectric constant.
Smart Images

Figure CN119613109A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of capacitors and relates to a ferroelectric ceramic material with a large dielectric constant in a wide temperature range and a preparation method thereof. Background Art
[0002] High dielectric constant capacitors refer to capacitors made of materials with higher dielectric constants. Dielectric constant is a physical quantity that describes the ability of a material to store electrical energy in an electric field. A high dielectric constant means that the material can store electrical energy more efficiently in an electric field. High dielectric constant capacitors generally have advantages such as larger capacitance, smaller volume, lower leakage current, higher operating voltage, and better thermal stability. High dielectric constant capacitors can achieve higher capacitance in a smaller volume, thus meeting the demand for high energy density in electronic devices. At the same time, they also have good stability and temperature resistance, and can maintain stable performance in harsh environments. Although high dielectric constant capacitors have many advantages, their manufacturing process is relatively complex and costly. In addition, as the temperature changes or the voltage increases, their dielectric constant and capacitance values may change, which may affect the performance of the circuit. Therefore, when selecting and using high dielectric constant capacitors, factors such as their temperature characteristics and voltage characteristics need to be fully considered.
[0003] In order to further optimize the performance of high dielectric constant capacitors, it is necessary to develop ferroelectric ceramic materials with both high dielectric constant and high temperature stability. However, high dielectric constant is usually difficult to achieve with good temperature stability, because high dielectric constant is usually achieved at the phase transition temperature, and when the temperature is far away from the phase transition temperature, the dielectric constant drops sharply, resulting in poor temperature stability. Therefore, high dielectric constant and temperature stability are usually not achieved at the same time.
[0004] High dielectric constant capacitors mainly use barium titanate materials, which have temperature characteristics such as X5R / X7R, that is, the capacitance changes greatly due to temperature. In addition, some other materials with high dielectric constants are also used to manufacture high dielectric constant capacitors, such as ceramic materials, polymer materials and thin film materials.
[0005] In recent years, experiments have found that at the four-phase junction of the phase diagram of the BaTiO3-based binary ferroelectric solid solution system, the paraelectric cubic phase (C), ferroelectric tetragonal phase (T), orthorhombic phase (O) and rhombohedral phase (R) converge, and the four-phase point presents a critical ferroelectric phase transition. Since the phase transition energy barrier of the critical ferroelectric phase transition is close to zero, the dielectric constant of these critical four-phase points is very large. However, the high dielectric constant of the critical four-phase point is difficult to be used in practice because their temperature stability is very low. When the temperature rises or falls, their dielectric constant drops sharply. Summary of the invention In view of the problems existing in the prior art, the present invention provides a method for preparing a material having a large dielectric constant within a large temperature range, so that the material has both a high dielectric constant and temperature stability.
[0006] The present invention is achieved through the following technical solutions: A ferroelectric ceramic material with a large dielectric constant in a wide temperature range, comprising a ferroelectric ceramic material prepared by laminating and compounding BZT-xBST ceramic embryos with 6 different additive components; The chemical formula of the BZT-xBST ceramic body is (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 O3 Among them, x is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 respectively.
[0007] A method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range, comprising: S1, based on (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 x in O3 is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 in different component ratios, weighing a mixture of raw materials including BaCO3, TiO2, BaZrO3 and SnO2, mixing them by ball milling once, and then pre-sintering to obtain a block material, grinding it into powder and then performing a second ball milling, and then drying to obtain BZT-xBST ceramic powders with different component ratios; S2, mixing BZT-xBST ceramic powders with different component ratios with a solvent, a dispersant, a plasticizer and a binder to obtain tape casting slurries with different component ratios; S3, performing vacuum degassing treatment on the tape casting slurries with different component ratios, and then performing tape casting drying to obtain BZT-xBST ceramic embryos with different component ratios; S4. The BZT-xBST ceramic embryos with different component ratios are heated and laminated to obtain ferroelectric ceramic green embryos, and then debinding and high-temperature sintering are performed in sequence to obtain ferroelectric ceramic materials with a large dielectric constant in a wide temperature range.
[0008] Preferably, in S2, the mass ratio of BZT-xBST ceramic powder to solvent, dispersant, binder and plasticizer is 55.0wt%: 39.5wt%: 0.5wt%: 4.0wt%: 1.0wt%.
[0009] Preferably, the specific process of S1 is: Based on (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 The x in O3 is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 in different component ratios, and a mixture of BaCO3, TiO2, BaZrO3 and SnO2 is weighed as raw materials, and the mixture of BaCO3, TiO2, BaZrO3 and SnO2: anhydrous ethanol: zirconium ball = 1:2:1 is ball-milled for 12 hours; the material after the first ball milling is washed and dried, and then pre-fired at 1300°C for 2 hours. The block material obtained by pre-fired is ground into powder, and then ball-milled for a second time for 12 hours at a mass ratio of powder: anhydrous ethanol = 1:2. After drying, BZT-xBST ceramic powders with different component ratios are obtained.
[0010] Preferably, the specific process of S2 is: The BZT-xBST ceramic powders with different component ratios were mixed with a solvent and a dispersant and ball-milled for 12 h, and then a binder and a plasticizer were added and the mixture was mixed and ball-milled for another 12 h to obtain tape casting slurries with different component ratios.
[0011] Preferably, the solvent is ethanol and ethyl acetate mixed in a volume fraction ratio of 3:7; the dispersant is oleic acid; the binder is polyvinyl butyral; and the plasticizer is at least one of polyethylene glycol and butyl phthalate.
[0012] Preferably, the specific process of S3 is: After the tape casting slurry with different component ratios was subjected to vacuum degassing for 20 min, the tape casting slurry after vacuum degassing was poured into the material tank of the tape casting machine and cast at a thickness of 400 μm at a rate of 3 cm / min and dried at 70°C for 24 h to obtain BZT-xBST ceramic embryos with different component ratios; Preferably, the specific process of S4 is: The BZT-xBST ceramic embryos with 6 different component ratios are cut into the same size, and heated and laminated for 5-10 minutes at a temperature of 80° C. and a pressure of 5-10 MPa to obtain a ferroelectric ceramic embryo; wherein the number of laminated layers is 16-32; The ferroelectric ceramic green body is heated to 550°C at a heating rate of 1-3°C / min under normal pressure and air atmosphere and kept warm for 30 min for debinding treatment to obtain a ferroelectric ceramic embryo. After the ferroelectric ceramic embryo is debinded, it is pressed with a zirconium plate, heated to 1460~1500°C at a heating rate of 3-5°C / min under air atmosphere and kept warm for 2h to complete high-temperature sintering, thereby obtaining a ferroelectric ceramic material with a large dielectric constant in a wide temperature range.
[0013] Preferably, when the dielectric constant of the ferroelectric ceramic material with a large dielectric constant in the wide temperature range is tested, the ferroelectric ceramic material is ground and polished, and then the single-sided smooth surface is gold-sprayed using a plasma magnetron sputtering coating apparatus, and plated with a Pt dot electrode with an electrode diameter of 1 mm.
[0014] Preferably, the ferroelectric ceramic material with a large dielectric constant in a wide temperature range undergoes a critical ferroelectric phase transition at a Curie temperature of 5° C. to 55° C.; The ferroelectric ceramic material with a large dielectric constant in a wide temperature range has a high dielectric property in a wide temperature range of 5°C to 55°C.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a ferroelectric ceramic material with a large dielectric constant in a wide temperature range and a preparation method thereof. The ferroelectric ceramic material is prepared by laminating and compounding BZT-xBST ceramic embryos of six components (x is 0.1, 0.2, 0.3, 0.4, 0.6, and 0.8, respectively) that undergo critical ferroelectric phase transitions in the ferroelectric ceramic material system; the chemical formula of the BZT-xBST ceramic embryo is (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 O3, by designing a layered structure on the critical line, a ferroelectric ceramic material was prepared by stacking and compounding 6 BZT-xBST ceramic embryos with different components, and successfully achieved high dielectric properties in a wide temperature range of 5°C to 55°C. This high dielectric constant in a wide temperature range (ε>21448) enables the ferroelectric ceramic material to exhibit excellent performance in a variety of application scenarios, such as capacitors, sensors, energy storage devices, etc., filling the blank area where it is difficult for existing ferroelectric ceramic materials to have both a wide temperature range and a high dielectric constant.
[0016] In the preparation method of the present invention, by precisely adjusting (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885The x value in O3 (0.1, 0.2, 0.3, 0.4, 0.6, 0.8) realizes the fine control of the components of ferroelectric ceramic materials. This precise ratio helps to optimize the ferroelectric and dielectric properties of the material, so that it exhibits a stable and excellent large dielectric constant in a wide temperature range. The ceramic embryos with different component ratios are heated and laminated to achieve uniform distribution of multiple components inside the material, which not only improves the overall performance of the material, but also enables it to maintain stable dielectric properties in different temperature ranges. The preparation method not only improves the dielectric properties of ferroelectric ceramic materials, but also reduces production costs and improves the application value of the material by optimizing the process steps and component ratios. The present invention further prepares multi-layer multi-critical phase change component ferroelectric ceramic materials through the design of a laminated structure of 6 components that undergo critical ferroelectric phase transitions, cleverly utilizing the characteristics of 6 different components undergoing critical ferroelectric phase transitions at different Curie temperatures in the range of 5-55°C. By rationally designing and combining ceramic embryos with different components, phase transitions can be induced within a specific temperature range, thereby significantly improving the dielectric properties of the material. Furthermore, the present invention successfully prepared (1-x)BaZr by using a tape casting method. 0.12 Ti0 0.88 O3-xBaSn 0.115 Ti 0.885 BZT-xBST ceramic embryo thick film of binary system of O3.
[0017] Furthermore, the process steps of primary ball milling, pre-sintering, grinding into powder, secondary ball milling and drying ensure the uniformity and purity of the ceramic powder. This optimized powder preparation process helps to improve the density and performance stability of ceramic materials.
[0018] Furthermore, after the treatment of debinding and high temperature sintering, the ceramic material obtains a dense microstructure and excellent performance. The high temperature sintering process helps to eliminate the pores and defects inside the material and improve the mechanical strength and dielectric properties of the ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a flow chart of the preparation method of the ferroelectric ceramic material of the present invention; Figure 2 is (1-x)BaZr 0.12 Ti0 0.88 O3-xBaSn 0.115 Ti 0.885 Schematic diagram of ceramic material design for the binary system of O3(BZT-xBST); Figure 3The dielectric temperature spectra of the multi-layer multi-component ceramic sheets of Example 1 and Example 2 with sintering and heat preservation time of 1h and 2h respectively; Figure (a) is Example 1, and Figure (b) is Example 2; Figure 4 is a comparison chart of the maximum dielectric constant and temperature range of the ferroelectric ceramic material of the present invention and other ferroelectric materials; DETAILED DESCRIPTION The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] Example 1 According to (1-x)BaZr 0.12 Ti0 0.88 O3-xBaSn 0.115 Ti 0.885 The x in O3 is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 respectively. The mass of BaCO3, TiO2, BaZrO3 and SnO2 raw materials is calculated and weighed to generate a 40g BZT-xBST ceramic body ratio, wherein the mass addition ratio of BaCO3, TiO2, BaZrO3 and SnO2 raw materials is shown in Table 1;
[0022] Weigh the mixed materials of BaCO3, TiO2, BaZrO3 and SnO2 with different component ratios in Table 1 above, and perform primary planetary ball milling for 12 h at a mass ratio of mixed material: anhydrous ethanol: zirconium ball = 1:2:1; wash the material after the primary ball milling into a glass petri dish, put it into an oven for drying, pour it into a quartz crucible, compact it, and put it into a muffle furnace for pre-calcining at 1300°C for 2 h; grind the pre-calcined block material into powder with a mortar, and then perform secondary ball milling for 12 h at a mass ratio of powder: anhydrous ethanol = 1:2; wash the material after the secondary ball milling into a glass petri dish, and after drying, obtain 6 BZT-xBST ceramic powders with different component ratios.
[0023] The BZT-xBST ceramic powders of 6 different components were mixed with solvent (the solvent was prepared by ethanol and ethyl acetate in a volume fraction ratio of 3:7 so that the two could be azeotropic at the same temperature point after mixing) and dispersant for 12 hours, and then the binder and plasticizer were added and mixed and milled for 12 hours to obtain 6 different component ratio casting slurries with uniform distribution and stable state; the above 6 different component ratio casting slurries were placed in a vacuum stirring degassing machine for 20 minutes of stirring, exhausting and degassing treatment. The mass fraction ratios of BZT-xBST ceramic powders with 6 different component ratios and solvents, dispersants, binders and plasticizers are 55.0wt%: 39.5wt%: 0.5wt%: 4.0wt%: 1.0wt%; among them, the plasticizer is 0.5wt% polyethylene glycol and 0.5wt% butyl phthalate; the dispersant is oleic acid; the binder is polyvinyl butyral; The six casting slurries with different component ratios after vacuum degassing treatment were poured into the material trough of the casting machine and cast at a thickness of 400 μm at a rate of 3 cm / min and dried at 70°C for 24 h to obtain BZT-xBST ceramic embryos with different component ratios; the dried BZT-xBST ceramic embryos with different component ratios were cut into suitable specifications as required, and the BZT-xBST ceramic embryos were heated and laminated at 80°C and 5 MPa for 10 min using a flat heating hydraulic press to obtain ferroelectric ceramic green embryos, wherein the number of laminated layers was 16, and the mature BZT-xBST ceramic embryos were cut or trimmed into small rectangles of 10 mm*10 mm as required.
[0024] The ferroelectric ceramic embryo was placed in a high-temperature muffle furnace, heated to 550°C at a heating rate of 1°C / min under normal pressure and air atmosphere and kept warm for 30 min for debinding treatment, and then cooled with the furnace to obtain a ferroelectric ceramic embryo; the debinded sample was placed in a high-temperature muffle furnace again, pressed with a small piece of zirconium plate to prevent deformation, heated to 1460°C at a heating rate of 3°C / min in air atmosphere and kept warm for 1 h to complete sintering, and a ferroelectric ceramic material with a large dielectric constant in a wide temperature range was obtained; after the ferroelectric ceramic material with a large dielectric constant in a wide temperature range was ground and polished, the single-sided smooth surface was gold-sprayed using a plasma magnetron sputtering coating instrument, and plated with a Pt point electrode with an electrode diameter of 1 mm for subsequent testing.
[0025] Example 2 The difference compared with Example 1 is that after the ferroelectric ceramic body is debinded, the temperature is increased to 1460° C. at a heating rate of 3° C. / min in an air atmosphere and kept at this temperature for 2 hours to complete sintering, thereby obtaining a ferroelectric ceramic material with a large dielectric constant in a wide temperature range; The rest of the preparation process is the same; Example 3 The difference compared with Example 1 is that the mass fraction ratio of the BZT-xBST ceramic powder with 6 different component ratios to the solvent, dispersant, binder and plasticizer is 55.0wt%: 39.5wt%: 0.5wt%: 4.0wt%: 1.0wt%; wherein the plasticizer uses 0.2wt% polyethylene glycol and 0.8wt% butyl phthalate; The rest of the preparation process is the same, and a ferroelectric ceramic material with a large dielectric constant in a wide temperature range is obtained; Example 4 The difference compared with Example 1 is that the mass fraction ratio of the 6 different component ratios of BZT-xBST ceramic powder to the solvent, dispersant, binder and plasticizer is 55.0wt%: 39.5wt%: 0.5wt%: 4.0wt%: 1.0wt%; wherein the plasticizer uses 1.0wt% of butyl phthalate; The rest of the preparation process is the same, and a ferroelectric ceramic material with a large dielectric constant in a wide temperature range is obtained; Example 5 The difference compared with Example 1 is that the BZT-xBST ceramic embryos with different composition ratios in 6 groups are cut into the same size, and are heated and laminated for 10 minutes under the conditions of temperature of 80° C. and pressure of 10 MPa to obtain ferroelectric ceramic embryos; wherein the number of laminated layers is 32; The ferroelectric ceramic green body was heated to 550°C at a heating rate of 3°C / min under normal pressure and air atmosphere and kept warm for 30 min for debinding treatment to obtain a ferroelectric ceramic embryo. After the ferroelectric ceramic embryo was debinded, it was pressed with a zirconium plate and heated to 1500°C at a heating rate of 5°C / min under air atmosphere and kept warm for 1h to complete high-temperature sintering to obtain a ferroelectric ceramic material with a large dielectric constant in a wide temperature range.
[0026] The rest of the preparation process is the same, and a ferroelectric ceramic material with a large dielectric constant in a wide temperature range is obtained; Example 6 The difference compared with Example 1 is that the BZT-xBST ceramic embryos with different composition ratios in 6 groups are cut into the same size, and are heated and laminated for 8 minutes under the conditions of temperature of 80° C. and pressure of 8 MPa to obtain ferroelectric ceramic embryos; wherein the number of laminated layers is 24; The ferroelectric ceramic green body is heated to 550°C at a heating rate of 2°C / min under normal pressure and air atmosphere and kept warm for 30 min for debinding treatment to obtain a ferroelectric ceramic embryo. After the ferroelectric ceramic embryo is debinded, it is pressed with a zirconium plate and heated to 1480°C at a heating rate of 4°C / min under air atmosphere and kept warm for 1h to complete high-temperature sintering to obtain a ferroelectric ceramic material with a large dielectric constant in a wide temperature range.
[0027] The rest of the preparation process is the same, and a ferroelectric ceramic material with a large dielectric constant in a wide temperature range is obtained; Figure 3 (a) and Figure 3 (b) shows the dielectric constant-temperature spectra of two multi-layer multi-component samples of Example 1 and Example 2 with sintering times of 1 hour and 2 hours respectively. Figure 3 From (a), it can be seen that the sample sintered for 1 hour has a significant dielectric peak platform in the temperature range of 5℃-55℃, and its dielectric constant is greater than 21448 in this temperature range. Figure 3 (b) It can be seen that the sample sintered for 2 hours has a higher dielectric constant in the temperature range of 20℃-48℃, and the dielectric constant is greater than 34087. The above results show that the designed material can maintain a high dielectric response capability in a wide temperature range and achieve high dielectric performance in a wide temperature range.
[0028] Figure 4 The maximum dielectric constant and temperature range (defined as the temperature range where the dielectric constant is greater than 90% of the maximum dielectric constant) of the two samples of Example 1 and Example 2 designed in this paper and other ferroelectric ceramic materials are compared. The results show that the temperature range of the laminated sample designed in this paper when the dielectric constant ε>21448 is 50K, and it has both a wide temperature range and a high dielectric constant, filling the blank area where the existing ferroelectric ceramic materials have difficulty in achieving both a wide temperature range and a high dielectric constant.
[0029] The preferred embodiments of the present invention are described in detail above. 0.12 Ti0 0.88 O3-xBaSn 0.115 Ti 0.885 By designing a layered structure on the critical line of O3 (BZT-xBST), a large dielectric constant is achieved in a wide temperature range of 5 to 55°C (ε>21448), filling the blank area where existing ferroelectric ceramic materials have difficulty in achieving both a wide temperature range and a high dielectric constant.
[0030] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A ferroelectric ceramic material having a large dielectric constant in a wide temperature range, characterized in that: Ferroelectric ceramic materials were prepared by laminating and compounding BZT-xBST ceramic embryos with 6 different component ratios; The chemical formula of the BZT-xBST ceramic body is (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 O3 Among them, x is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 respectively.
2. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range as claimed in claim 1, characterized in that: include: S1, based on (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 x in O3 is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 in different component ratios, weighing a mixture of raw materials including BaCO3, TiO2, BaZrO3 and SnO2, mixing them by ball milling once, and then pre-sintering to obtain a block material, grinding it into powder and then performing a second ball milling, and then drying to obtain BZT-xBST ceramic powders with different component ratios; S2, mixing BZT-xBST ceramic powders with different component ratios with a solvent, a dispersant, a plasticizer and a binder to obtain tape casting slurries with different component ratios; S3, performing vacuum degassing treatment on the tape casting slurries with different component ratios, and then performing tape casting drying to obtain BZT-xBST ceramic embryos with different component ratios; S4. The BZT-xBST ceramic embryos with different component ratios are heated and laminated to obtain ferroelectric ceramic green embryos, and then debinding and high-temperature sintering are performed in sequence to obtain ferroelectric ceramic materials with a large dielectric constant in a wide temperature range.
3. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 2, characterized in that: In S2, the mass ratio of BZT-xBST ceramic powder to solvent, dispersant, binder and plasticizer is 55.0wt%: 39.5wt%: 0.5wt%: 4.0wt%: 1.0wt%.
4. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 2, characterized in that: The specific process of S1 is: Based on (1-x)BaZr 0.12 Ti0 0.88 O 3- xB 0.115 Ti 0.885 The x in O3 is 0.1, 0.2, 0.3, 0.4, 0.6 and 0.8 in different component ratios, and a mixture of BaCO3, TiO2, BaZrO3 and SnO2 is weighed as raw materials, and the mixture of BaCO3, TiO2, BaZrO3 and SnO2: anhydrous ethanol: zirconium ball = 1:2:1 is ball-milled for 12 hours; the material after the first ball milling is washed and dried, and then pre-fired at 1300°C for 2 hours. The block material obtained by pre-fired is ground into powder, and then ball-milled for a second time for 12 hours at a mass ratio of powder: anhydrous ethanol = 1:
2. After drying, BZT-xBST ceramic powders with different component ratios are obtained.
5. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 2, characterized in that: The specific process of S2 is: The BZT-xBST ceramic powders with different component ratios were mixed with a solvent and a dispersant and ball-milled for 12 h, and then a binder and a plasticizer were added and the mixture was mixed and ball-milled for another 12 h to obtain tape casting slurries with different component ratios.
6. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 5, characterized in that: The solvent is prepared by mixing ethanol and ethyl acetate in a volume fraction ratio of 3:
7.
7. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 5, characterized in that: The dispersant is oleic acid; the binder is polyvinyl butyral; and the plasticizer is at least one of polyethylene glycol and butyl phthalate.
8. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 2, characterized in that: The specific process of S3 is: The casting slurry with different component ratios was subjected to vacuum degassing for 20 min, then poured into the casting machine trough and cast at a thickness of 400 μm at a rate of 3 cm / min and dried at 70°C for 24 h to obtain BZT-xBST ceramic embryos with different component ratios.
9. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 2, characterized in that: The specific process of S4 is: The BZT-xBST ceramic embryos with 6 different component ratios are cut into the same size, and heated and laminated for 5-10 minutes at a temperature of 80° C. and a pressure of 5-10 MPa to obtain a ferroelectric ceramic embryo; the number of laminated layers is 16-32; The ferroelectric ceramic green body is heated to 550°C at a heating rate of 1-3°C / min under normal pressure and air atmosphere and kept warm for 30 min for debinding treatment to obtain a ferroelectric ceramic embryo. After the ferroelectric ceramic embryo is debinded, it is pressed with a zirconium plate, heated to 1460~1500°C at a heating rate of 3-5°C / min under air atmosphere and kept warm for 2h to complete high-temperature sintering, thereby obtaining a ferroelectric ceramic material with a large dielectric constant in a wide temperature range.
10. The method for preparing a ferroelectric ceramic material having a large dielectric constant in a wide temperature range according to claim 2, characterized in that: The ferroelectric ceramic material with a large dielectric constant in a wide temperature range undergoes a critical ferroelectric phase transition at a Curie temperature of 5°C to 55°C; the temperature range of the wide temperature range high dielectric performance of the ferroelectric ceramic material with a large dielectric constant in a wide temperature range is 5°C to 55°C.
Citation Information
Patent Citations
Multilayer gradient Ba1-xSrxTiO3 (BST) dielectric ceramic material and preparation method
CN101863154A
Wide-temperature-range linear dielectric ceramic material and preparation method thereof
CN111892397A
Non-plumbum series ferroelectric film with ingredient gradient distribution and its preparation method
CN1880275A
Composite material and method for producing composite material and its use as capacitor material
EP4112580A1